Nowcasting unemployment rates with Google searches: Evidence from the Visegrad Group countries - Jaroslav Pavlicek; Ladislav Kristoufek (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
The online activity of Internet users has repeatedly been shown to provide a rich information set for various research fields. We focus on job-related searches on Google and their possible usefulness in the region of the Visegrad Group - the Czech Republic, Hungary, Poland and Slovakia. Even for rather small economies, the online searches of inhabitants can be successfully utilized for macroeconomic predictions. Specifically, we study unemployment rates and their interconnection with job-related searches. We show that Google searches enhance nowcasting models of unemployment rates for the Czech Republic and Hungary whereas for Poland and Slovakia, the results are mixed.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E24; E27; J64; 330; unemployment; Google Trends; nowcasting